2012
DOI: 10.1021/bi300477z
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Benzoquinones to Hydroquinones via Spontaneous Reaction with Glutathione and Enzymatic Reaction by S-Glutathionyl-Hydroquinone Reductases

Abstract: S-Glutathionyl-hydroquinone reductases (GS-HQRs) are a new class of glutathione transferases, widely present in bacteria, halobacteria, fungi, and plants. They catalyze glutathione (GSH)-dependent reduction of GS-trichloro-p-hydroquinone to trichloro-p-hydroquinone. Since GS-trichloro-p-hydroquinone is uncommon in nature, the extensive presence of GS-HQRs suggests they use common GS-hydroquinones. Here we demonstrate that several benzoquinones spontaneously reacted with GSH to form GS-hydroquinones via Michael… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…8). We have shown that GSH removal can also be established by other thiol-containing compounds, such as L-cysteine, DTT, and 2-mercaptoethanol (4) or even by the reducing agent NaBH 4 (7). This reaction scheme is in agreement with our previous kinetic analysis that PcpF catalyzes GSH-dependent reduction of GS-TriCH via a ping-pong mechanism (4).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…8). We have shown that GSH removal can also be established by other thiol-containing compounds, such as L-cysteine, DTT, and 2-mercaptoethanol (4) or even by the reducing agent NaBH 4 (7). This reaction scheme is in agreement with our previous kinetic analysis that PcpF catalyzes GSH-dependent reduction of GS-TriCH via a ping-pong mechanism (4).…”
Section: Discussionsupporting
confidence: 89%
“…For example, PcpF is able to deglutathionylate S-(phenacyl) glutathione, but EcYqjG, CnYqjG, and ECM4 PcGHR1 do not use it as a substrate (5). In addition, the specific enzyme activity varied among these enzymes (7). Therefore, in lieu of bioremediation applications, in-depth investigation of GS-HQRs could provide a new approach for treating environmental pollutants that produce various quinone intermediates during biodegradation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations